Inhibitory effect of Aphidicolin - a tetracyclic diterpene - on the proliferation and apoptotic induction in human cervical cancer (HeLa) cells - Yu, En-Yan; Zhao, Rui Yan; Wang, Dong Sheng (Journal of B.U.ON. : official journal of the Balkan Union of Oncology, 2021)
Retraction of: 'Inhibitory effect of Aphidicolin - a tetracyclic diterpene - on the proliferation and apoptotic induction in human cervical cancer (HeLa) cells', by En-Yan Yu, Rui-Yan Zhao, Dong-Sheng Wang, JBUON 2015;20(6):1480-1486; PMID:26854444. Following the publication of the above article, readers drew to our attention that part of the data was unreliable. The authors were requested to provide the raw data to prove the originality, but were unable to do so. After an investigation, the Editors of JBUON decided to retract this article. We thank the readers for bringing this matter to our attention. We apologize for any inconvenience it may cause.